1995
DOI: 10.1111/j.1751-1097.1995.tb02369.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nf‐kb in Human Skin Fibroblasts by the Oxidative Stress Generated by Uva Radiation

Abstract: We have examined the role of the nucleus and the membrane in the activation of nuclear factor (NF)-kappa B by oxidant stress generated via the UVA (320-380 nm) component of solar radiation. Nuclear extracts from human skin fibroblasts that had been irradiated with UVA at doses that caused little DNA damage contained activated NF-kappa B that bound to its recognition sequence in DNA. The UVA radiation-dependent activation of NF-kappa B in enucleated cells confirmed that the nucleus was not involved. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 33 publications
1
84
1
Order By: Relevance
“…The only previous study examining the effects of EGCG on UVA radiation reported its reduction of UVA-induced AP-1 and NF-KB transcription factor activities, 32 processes known to be affected by redox status 33,34 thus providing additional evidence for EGCG antioxidant action against UVA. Wei et al 15 also reported the protection afforded by a green tea fraction containing a number of polyphenols against UVA-induced oxidative damage but only in a DNA solution.…”
Section: Discussionmentioning
confidence: 99%
“…The only previous study examining the effects of EGCG on UVA radiation reported its reduction of UVA-induced AP-1 and NF-KB transcription factor activities, 32 processes known to be affected by redox status 33,34 thus providing additional evidence for EGCG antioxidant action against UVA. Wei et al 15 also reported the protection afforded by a green tea fraction containing a number of polyphenols against UVA-induced oxidative damage but only in a DNA solution.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-kB transcription factor has emerged as a central component of the inductile cellular signaling machinery that serves as an important regulatory role in inflammation, immunity, cell proliferation, and oncogenesis (Thanos and Maniatis, 1995;Baeuerle and Baltimore, 1996;Baldwin, 1996;Maniatis, 1997). NF-kB is activated by oxidant including H 2 O 2 (Ikeda et al, 2002) and by agents that generate ROS such as UV radiation (Vile et al, 1995;Legrand-Poels et al, 1998;Helenius et al, 1999), phorbol myristate acetate (Haas et al, 1998;Majumdar et al, 2002), and tumor necrosis factor-a (TNF-a) (Schreck et al, 1991;Devary et al, 1993). Compounds that scavenge ROS inhibit NF-kB activa- Figure 4 Inhibitory effect of EGCG on UVB-induced activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…NFκB is ubiquitously expressed in an inactive form in most cells, composed of NFκB p50 and Rel A p65 subunits, and bound to an inhibitory protein, Iota kappa B alpha (ΙκBα). In response to various stimuli, including UVA/UVB light, inflammatory cytokines, DNA damage and variety of mitogens, cytokine is activated and regulates genes involved in inflammation, immunity, cell cycle progression, apoptosis, and oncogenesis 7,50,51 . NF-κB activation contributes to the production of interleukins or TNF-α and seems to be subject to redox regulation, suggesting thus an important role of antioxidants in its inactivation.…”
Section: Activation Of Cell Survival and Proliferationmentioning
confidence: 99%